1981
DOI: 10.1111/j.1365-2672.1981.tb04247.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological Examination of Pipeline Milking Machines by Rinsing the Entire System

Abstract: The results of bacteriological examination of rinses of the entire systems of 12 pipeline milking machines were compared with a similar examination of the milk collected while they were used for milking. The machines were cleaned in three different ways and showed varying degrees of complexity. There was a close correlation between the results when the milk was collected with the maximum of cleanliness during milking. This is attributed to the localization of most of the micro-organisms present in the milking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1981
1981
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…As observed in the present study, different parts of the milking machine can vary in bacterial counts. In this regard, Richard (1981) indicated that most microorganisms are present in the joints and complex parts of the milking machine and not on the surface of the equipment. Therefore, the profound cleanliness of milking equipment is necessary to reduce the number of microorganisms present in the milking machine.…”
Section: Bacteriological Count In Milking Machine Partsmentioning
confidence: 99%
“…As observed in the present study, different parts of the milking machine can vary in bacterial counts. In this regard, Richard (1981) indicated that most microorganisms are present in the joints and complex parts of the milking machine and not on the surface of the equipment. Therefore, the profound cleanliness of milking equipment is necessary to reduce the number of microorganisms present in the milking machine.…”
Section: Bacteriological Count In Milking Machine Partsmentioning
confidence: 99%